Longitudinal Follow‐Up of the Specific Antibody Response to SARS‐CoV‐2 Vaccination in Colombia - Arévalo‐Herrera, Myriam; Rincón‐Orozco, Bladimiro; González‐Escobar, John Mario; Herrera‐Arévalo, Sonia Marcela; Carrasquilla‐Agudelo, Elena; Serna‐Ortega, Paula Andrea; Quiceno‐García, Sebastián; Palacio‐Muñoz, Nicolas; Rosero‐López, Brandon; Mondol‐Miranda, Ernesto; Freyle‐Roman, Ivette; Mendoza‐Landinez, Brayan; et al. (Journal of medical virology, 2025)
ABSTRACT A total of 5011 adult volunteers attending vaccination centers in different regions of Colombia were enrolled in a 1‐year prospective observational cohort study to evaluate the immunogenicity and effectiveness of SARS‐CoV‐2‐based vaccines as part of a National Vaccine Program established to contain the COVID‐19 pandemic. Following informed consent, 5,011 participants underwent a sociodemographic survey and PCR testing to assess SARS‐CoV‐2 infection. Blood samples were collected, and serum fractions were obtained from a participant subsample (n = 3441) at six‐time points to assess virus‐specific IgG responses to the Spike protein, its Receptor Binding Domain, and the Nucleoprotein by ELISA. Additionally, antibody‐neutralizing activity was evaluated using a cPass SARS‐CoV‐2 neutralization kit. Most participants (95.8%; n = 4802) received between one Ad26. COV2.S (Janssen vaccine) and four vaccine doses of BNT162b2 (Pfizer/BioNTech), AZD1222 (AstraZeneca), mRNA‐1273 (Moderna), CoronaVac (Sinovac), with some receiving vaccine combinations; a small group, 4.2% (n = 209), remained unvaccinated. Throughout the study, only 8.76% (n = 439) of the participants tested positive for SARS‐CoV‐2 by PCR. Notably, all participants seroconverted for IgG antibodies, with high seropositivity rates for S (99.8%; n = 4795), RBD (99.7%; n = 1691), and N (92.7%; n = 3072) proteins. Moreover, significant (92%–97%) neutralizing activity was observed for all four SARS‐CoV‐2 circulating variants. This study highlights the importance of assessing the duration of the IgG response to SARS‐CoV‐2 elicited by vaccination and infection, and the antibody neutralizing activity as a potential surrogate marker of protection. These findings provide important insight for further strengthening the vaccination strategies to control COVID‐19.